Digital Skills as Success Factors in TVET Entrepreneurship Education: A Systematic Review - Mustaffa, Mastura; Selvaratnam, Doris Padmini S.; Tawil, Norngainy Mohd; Affandi, Haryanti Mohd (Journal of Ecohumanism, 2025)
This study aims to investigate the significance of digital skills as determinants of success in Technical and Vocational Education and Training (TVET) entrepreneurship education by conducting a systematic literature review. The progression of the study complies with the PRISMA framework to ensure a thorough and transparent approach. Research, experiments, and implementation strategies related to digital skills and entrepreneurship in TVET were all included in the extensive and detailed examination of current research. An advanced search technique was employed using keywords such as "digital skill," "success," "entrepreneurship," "education," and "TVET" across reputable databases, including Scopus, Web of Science (WoS), and ERIC. The inclusion criteria focused on peer-reviewed articles published between 2020 and 2024, yielding a final selection of 19 studies as the primary data source. A mixed-method approach was applied to analyse the findings systematically. The results of the review were categorized into three main themes: (1) digital competence, (2) digital education and training, and (3) entrepreneurial development. Digital competence emerged as the dominant theme, emphasizing the importance of technical proficiency, critical problem-solving, and the effective use of digital tools in enhancing entrepreneurial success. Digital education and training fostered digital literacy through hands-on learning approaches, real-world case studies, and competency-based learning methods. On the other hand, entrepreneurial development highlighted the need for building self-efficacy, leadership, creativity, and digital readiness among TVET students. The study concludes that integrating digital skills into TVET entrepreneurship education is critical for preparing graduates to thrive in the digital economy. Addressing challenges such as infrastructure gaps, limited access to technology, and the need for industry-aligned curricula can enable TVET institutions to cultivate innovative, adaptable, and forward-thinking entrepreneurs. This integration ultimately has the potential to drive sustainable economic growth and enhance graduate employability in the digital era.